Preparation, characterization and immunomodulatory effects of unsaturated sulfated oligoguluronic acid. (1st February 2023) - Bi, Decheng; Huang, Jinfeng; Cao, Jue; Yao, Lijun; Guo, Wushuang; Zhang, Zhenqing; Wu, Yan; Xu, Hong; Hu, Zhangli; Xu, Xu
Abstract: Polyguluronic acid (PG) is a type of polysaccharide found in edible brown seaweeds. This study synthesized a new sulfated saccharide (SOGA) by sulfating PG-derived unsaturated oligoguluronic acid (OGA). The molecular weight and degree of sulfate-group substitution of SOGA were 1.6 kDa and 1.03, respectively. The structures of PG, OGA, and SOGA were elucidated using FT-IR and NMR spectroscopy. Furthermore, the immunomodulatory effects of PG, OGA, and SOGA on LPS-triggered RAW264.7 and BV2 cells were evaluated. SOGA, but not PG or OGA, significantly reduced the LPS-stimulated overproduction of proinflammatory mediators and suppressed the activation of corresponding signalling pathways. Also, SOGA could actively regulate immune balance by inhibiting apoptosis and pyroapoptosis. These results suggested that SOGA is a potential therapeutic agent for the prevention of diseases associated with immune disorders owing to its remarkable immunomodulatory effects, and that sulfate groups in the carbohydrate chain play a crucial role for its bioactivities. Graphical abstract: Unlabelled Image